Antibiotic-resistant bacteria and gut microbiome communities associated with wild-caught shrimp from the United States versus imported farm-raised retail shrimp - Laxmi Sharma; Ravinder Nagpal; Charlene R. Jackson; Dhruv Patel; Prashant Singh (Scientific Reports, 2021)
Abstract In the United States, farm-raised shrimp accounts for ~ 80% of the market share. Farmed shrimp are cultivated as monoculture and are susceptible to infections. The aquaculture industry is dependent on the application of antibiotics for disease prevention, resulting in the selection of antibiotic-resistant bacteria. We aimed to characterize the prevalence of antibiotic-resistant bacteria and gut microbiome communities in commercially available shrimp. Thirty-one raw and cooked shrimp samples were purchased from supermarkets in Florida and Georgia (U.S.) between March–September 2019. The samples were processed for the isolation of antibiotic-resistant bacteria, and isolates were characterized using an array of molecular and antibiotic susceptibility tests. Aerobic plate counts of the cooked samples (n = 13) varied from < 25 to 6.2 log CFU/g. Isolates obtained (n = 110) were spread across 18 genera, comprised of coliforms and opportunistic pathogens. Interestingly, isolates from cooked shrimp showed higher resistance towards chloramphenicol (18.6%) and tetracycline (20%), while those from raw shrimp exhibited low levels of resistance towards nalidixic acid (10%) and tetracycline (8.2%). Compared to wild-caught shrimp, the imported farm-raised shrimp harbored distinct gut microbiota communities and a higher prevalence of antibiotic-resistance genes in their gut. The presence of antibiotic-resistant strains in cooked shrimps calls for change in processing for their mitigation.